The Significance of Distribution Channel And Product Life Cycle In The Management of An Organization The Nigerian Experience (Global Journal of Management and Business Research, 2011)
In recent times, business organizations operate on large and specialized, scales, which have all, resulted in increased production. As a result of this increased production, direct marketing to consumers had become very expensive and inefficient. Marketing channel decisions are among the most complex and challenging decisions facing the firm As man passes his life in phases: birth, childhood, adolescence, adulthood, old age and death so do products as evidenced in the product life cycle theory. The objectives of this paper are to assess the significance of distribution channel and product life cycle on the survival and growth of business organizations in Nigeria. Efforts are made to discuss in details the conceptual framework of distribution channel and product/life cycle. Finally it is posited that distribution channel and product life cycle are highly significant in the management.This paper is divided into four sections namely: introduction, distribution channel, product life cycle and conclusion and recommendations.
Keywords: birth; childhood; adolescence; adulthood